Rumours of war : de-constructing media discourses of HIV/AIDS in South Africa - Connelly, Mark (Rhodes University, Faculty of Humanities, Department of Psychology, 2002)
This paper explores discourses of HIV/AIDS evident in a South African daily newspaper from 1985 to 2000, and discusses the implications of these in terms of the way in which HIV/AIDS is constructed in society. In this paper I utilize a Foucauldian analysis of the relationship between power and knowledge. The discursive framework of the war against HIV/AIDS is used to show how different groups of subjects are positioned in relations of power. Within this the power of western science and medicine is influential and supports and informs other discourses of HIV/AIDS. I argue that the discursive framework constructing HIV/AIDS as a war does far more than provide a useful vehicle within which HIV/AIDS can be understood as it supports certain institutions and groups of people above others. The paper concludes by identifying the silenced voices of women and dissidents, and calling for greater reflection concerning the critical analysis of current issues surrounding HIV/AIDS.
Keywords: AIDS (Disease) -- South Africa; AIDS (Disease) in mass media